The work motivation of the industrial supervisor. - Chapman, A. M. P. (Cranfield University, 1982)
The study examines the effect of role ambiguity as experienced by production supervisors, upon their attitudes to work and investigates the supervisory role with reference to perceptions of managers and supervisors. Role ambiguity is considered by several theorists to have a negative influence upon work attitudes generally. The study aims to identify which work attitudes are most significantly influenced and how much the presence and level of role ambiguity explains the variation in levels of motivation of supervisors. The sample of supervisors and managers for the pilot study was drawn from 3 manufacturing organisations in the food industry, the main study relies on a sample of supervisors and managers from 6 organisations. Whilst the major research objective has been to examine the effect of role ambiguity upon supervisors' attitudes, a significant element of the research has been directed towards clarification of the supervisory role, investigating such commonly-quoted situations as the supervisor as the "man in the middle" who suffers more than others in the organisation from role ambiguity. The practical outcomes of the research are presented with reference to their use and potential value in an organisational context. The findings of the study indicate significant relationships in 5 out of the 6 predicted associations comprising the hypotheses. The theoretical model which has been developed lacks power as an explanatory instrument. The model is useful, however, as a descriptive tool, relating some of the variables which are associated with supervisors' work motivation.